DAMPAK PENILAIAN PRESTASI, MOTIVASI, DAN DISIPLIN KARYAWAN ATAS PROMOSI JABATAN - Damayanti, Reina; Kurbani, Adie; Ariyanto, Defri (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study examines the effect of performance appraisal, work motivation, and discipline on promotion at PT Pertamina Patra Niaga IT Kertapati Palembang. The population in this study were employees who worked at PT Pertamina Patra Niaga IT Kertapati Palembang with a total of 159 employees. Sampling was carried out using the probability sampling method, and then a sample of 62 employees who will be the respondents was generated. The measurement scale used in this study is the Likert scale. This research uses analysis techniques of validity test, reliability test, classic assumpton test, simple regression analysis, multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing which consists of F test (simultaneous) and t-test (partial). The results of this study concluded that partial and simultaneous assessment of work performance, motivation, and work discipline had a significant effect on promotion at PT Pertamina Patra Niaga IT Kertapati Palembang. Keywords: Performance Appraisal; Motivation; Work Discipline; Job Promotion